2020
DOI: 10.1371/journal.pntd.0008434
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dengue forecast for outbreak alerts in Southern Taiwan

Abstract: Dengue fever is a viral disease transmitted by mosquitoes. In recent decades, dengue fever has spread throughout the world. In 2014 and 2015, southern Taiwan experienced its most serious dengue outbreak in recent years. Some statistical models have been established in the past, however, these models may not be suitable for predicting huge outbreaks in 2014 and 2015. The control of dengue fever has become the primary task of local health agencies. This study attempts to predict the occurrence of dengue fever in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this study, we found large differences in absolute FI and GI values as well as trends. When analyzing trap indices and weather records, we noted that the temperatures of the entire study period were in the suitable range for short gonotrophic cycles and high biting rates in mosquito populations ( 36 , 37 ). Furthermore, weeks 24, 29, 33, and 34 had total rainfall above 200 mm ( Figure 2C ), which increased FI but caused minimal changes in GI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found large differences in absolute FI and GI values as well as trends. When analyzing trap indices and weather records, we noted that the temperatures of the entire study period were in the suitable range for short gonotrophic cycles and high biting rates in mosquito populations ( 36 , 37 ). Furthermore, weeks 24, 29, 33, and 34 had total rainfall above 200 mm ( Figure 2C ), which increased FI but caused minimal changes in GI.…”
Section: Discussionmentioning
confidence: 99%
“…We used the RMSE as a measure of the model’s predictive performance in the Alpha & Delta period, as in several previous studies [ 17 , 55 , 71 , 72 ]: where is the actual number of dependent variables at time t , is the forecast dependent variable value, and n is the sample size. Lower values reflect more accurate forecasting.…”
Section: Methodsmentioning
confidence: 99%
“…Such forecasting is an essential part of public health policy, guiding the timely implementation of vector control operations and mitigating outbreak risks. It has been used successfully during pandemics/epidemics of influenza (H1N1-2009) [ 16 ], dengue fever [ 17 , 18 ], and Ebola [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various epidemiological transmissions of infectious diseases, such as diarrhea, typhoid, malaria, and dengue fever, can be approximated using spatial models by enhancing the effectiveness of treatments that will lead to improved results (Phanitchat et al, 2019). A study in Kaohsiung City, Southern Taiwan, looked at the association between climatic conditions and the dengue outbreak and discovered that humidity and bite rates were substantially connected with cases of dengue disease (Cheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%